Pengambilan Keputusan sebagai Wirausaha Muda dan Faktor Eksternal yang Memengaruhinya di Institut Bisnis dan Informatika Stikom Surabaya - Candraningrat, Candraningrat (Jurnal Bisnis dan Keuangan, 2017)
lyze the influence of external factors consisting of family support and Business capital to the students decision-making at the Business Faculty of the Institut Bisnis dan Informatika Stikom Surabaya. The research was conducted from 42 students were taken by the purposive sampling method which were active students who own businesses or who are interested in entrepreneurship in the future, survey method used for data gathering with instrument questionnaire and analyzed by SPSSversion 21 to examine the research hypothesis. The result of multiple regression analysis showed that the variable family role and business capital is predicted to increase the student interest in entrepreneurship therefore the stated hypothesis 1 were accepted, but as partially the role of family able to increase the interest in entrepreneurship of the student, although that business capital not necessarily increase the interest of the students to entrepreneurship so the second hypothesis was rejected..